Development of the Traditional Rainbow Rope Game as a Medium for Gross Motor Stimulation of Children Aged 5-6 Years - Istiqomah Istiqomah; Ferdian Utama; Yuning Eka Rahma Wati (Bulletin of Early Childhood, 2026)
This research is motivated by the low gross motor skills of children aged 5-6 years at PAUD KB Al Ikhlash Gaya Baru III Central Lampung which is caused by the lack of interesting and interactive learning media variations. The purpose of this study is to develop and determine the effectiveness of the traditional rainbow rope game as a medium for stimulating gross motor skills in early childhood. This study uses the Research and Development (R&D) method with the Borg and Gall model which is simplified into seven stages, namely potential and problems, data collection, product design, design validation, design revision, product trials, and product revisions. The research subjects consisted of media experts, material experts, and 16 children aged 5-6 years. Data collection techniques used observation, interviews, questionnaires, and documentation, while data analysis was carried out qualitatively and quantitatively. The results showed that the traditional rainbow rope game was declared very feasible by media experts with an average score of 3.80 and feasible by material experts with an average score of 3.00. Furthermore, the trial results showed an improvement in children's gross motor skills, indicated by a decrease in the Not Yet Developed (BB) category and an increase in the Developing as Expected (BSH) and Very Well Developed (BSB) categories. Thus, the traditional rainbow rope game is an effective learning tool to stimulate gross motor skills in early childhood in a fun and interactive way.